SISTEM INFORMASI GEOGRAFIS BERBASIS WEB OBJEK WISATA DI KABUPATEN MINAHASA UTARA - Misheila Kalempouw; Marline S. Paendong; Winsy Ch. D. Weku; Mahardika I. Takaendengan (Indonesian Journal of Intelligence Data Science, 2023)
North Minahasa Regency has so many tourist objects spread across almost all sub-districts in North Minahasa Regency. Web-based Geographic information system for tourism objects in North Minahasa Regency is one of the tools to convey information as well as promotional media about tourism objects in North Minahasa Regency. This geographic information system is made web-based with the system development method, namely the waterfall method. This application uses PHP (Hypertext Preprocessor) as a programming language, uses MySQL as a data storage area and is assisted by Sumblime Text as a text editor. Making this web-GIS starts from data collection, namely spatial data in the form of a map of the North Minahasa Regency area along with the coordinates of tourist attractions in North Minahasa Regency. Then the process will be continued by making a web, namely designing a web appearance and the process of creating a web page. The end result of this process will be the formation of a Geographic Information System Website for tourist attractions in North Minahasa Regency which would make it easier for tourists to obtain information on the location of tourist attractions in North Minahasa Regency.